Green synthesis of some iron oxide nanoparticles and their interaction with 2-Amino, 3-Amino and 4-Aminopyridines. (2016) - Jassal, Vidhisha; Shanker, Uma; Gahlot, Sweta
Abstract: A green route was successfully used to synthesize Iron Oxide nanoparticles (α-FeOOH, β-FeOOH and α-Fe2 O3 ). This approach involves use of Sapindus mukorossi (raw reetha) as a natural surfactant and water as a solvent. All the synthesized nanoparticles were formed below 100 nm with rod-like morphology. It must be emphasized here that during the synthesis of nanoparticles, no harmful toxic solvent or chemicals were used. This approach utilizes Sapindus mukorossi, a natural product with properties of surfactant. The synthesized nanoparticles were characterized by Powder X-ray diffraction (PXRD), Field-Emission Scanning electron microscopy (FE-SEM) and Transmission electron microscopy (TEM). The iron oxide nanoparticles synthesized were successfully utilized in the interaction of 2, 3 and 4-Aminopyridines. α-FeOOH was found to be the most efficient catalyst for the adsorption of Aminopyridines, probably due to its higher surface area among other iron oxides used.